Transcriptional Profiling of Mycobacterium Tuberculosis During Infection: Lessons Learned - Ward, Sarah K.; Abomoelak, Bassam; Marcus, Sarah; Talaat, Adel M. (Frontiers in Microbiology, 2010)
Infection with Mycobacterium tuberculosis, the causative agent of tuberculosis, is considered one of the biggest infectious disease killers worldwide. A significant amount of attention has been directed towards revealing genes involved in the virulence and pathogenesis of this air-born pathogen. With the advances in technologies for transcriptional profiling, several groups, including ours, took advantage of DNA microarrays to identify transcriptional units differentially regulated by M. tuberculosis within a host. The main idea behind this approach is that pathogens tend to regulate their gene expression levels depending on the host microenvironment, and preferentially express those needed for survival. Identifying this class of genes will improve our understanding of pathogenesis. In our case, we identified an in vivo expressed genomic island (iVEGI) that was preferentially activate in murine lungs during early infection, as well as groups of genes activate during chronic tuberculosis. Other studies have identified additional gene groups that are active during macrophage infection and even in human lungs. Despite all of these findings, one of the lingering questions remaining was whether in vivo expressed transcripts are relevant to the virulence, pathogenesis, and persistence of the organism. The work of our group and others addressed this question by examining the contribution of in vivo expressed genes using a strategy based on gene deletions followed by animal infections. Overall, the analysis of most of the in vivo expressed genes supported a role of these genes in M. tuberculosis pathogenesis. Further, these data suggest that in vivo transcriptional profiling is a valid approach to identify genes required for bacterial pathogenesis.